Integrating Treatment of Neutralization with Sulfidic Natural Water (SNW) to Capture Dissolved Copper (Cu2+) from Acid Mine Drainage (AMD) at Batu Hijau Site, Sumbawa Island Indonesia - Surya Hadi; Ni Made Sri Suliartini; Lely Kurniawati; Surayyal Hizmi (Universitas Gadjah Mada, 2018)
The overall objectives of the research were (1) to study the capability of sodium hydrosulfide (NaHS) and sulfidic natural water (SNW) of Sebau in recovery of Cu2+, (2) to investigate the potency of integrating treatments of neutralization with sulfidization using SNW of Sebau in removing Cu2+ from acid mine drainage (AMD) collected from Batu Hijau site. The first objective was achieved by separately reacting (in situ) NaHS and SNW with a Cu2+ solution at pH 5.5. The second objective was answered by conducting treatments of lime-neutralization by the use of three levels of pH (4.0; 5.5; 7.0) and sulfidization using SNW collected from Sebau, Lombok Island at three sampling points. The result showed that NaHS (61.6 mg/L) could precipitate Cu2+ solution (44.45 mg/L) up to 71.3%, while SNW of Sebau could precipitate Cu2+ solution (44.45 mg/L) for almost 100% at pH 5.5. The results also revealed that SNW could precipitate the remained Cu2+ in the AMD from the neutralization treatment (pH 4 = 113.5 mg/L; pH 5.5 = 85.01 mg/L; and pH 7.0 = 2.372 mg/L) to 83.84% (pH = 4.0) and 100% (pH = 5.5 and 7.0). Although both pH 5.5 and 7.0 could completely precipitate Cu2+ in the AMD, by comparing the experimental result with the stoichiometric analysis, it was predicted that pH 5.5 was an optimum pH level for the reaction between AMD and SNW to recover Cu2+ in the AMD. Without neutralization treatment, SNW showed potentiality to recover Cu2+ since the combination treatments of neutralization at pH 4 with SNW collected from three sample points resulted in a high percent recovery of Cu2+.